2021
DOI: 10.1136/bmjopen-2021-053036
|View full text |Cite
|
Sign up to set email alerts
|

Passive and active immunity in infants born to mothers with SARS-CoV-2 infection during pregnancy: prospective cohort study

Abstract: ObjectiveTo investigate maternal immunoglobulins’ (IgM, IgG) response to SARS-CoV-2 infection during pregnancy and IgG transplacental transfer, to characterise neonatal antibody response to SARS-CoV-2 infection, and to longitudinally follow actively and passively acquired antibodies in infants.DesignA prospective observational study.SettingPublic healthcare system in Santa Clara County (California, USA).ParticipantsWomen with symptomatic or asymptomatic SARS-CoV-2 infection during pregnancy and their infants w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 40 publications
(38 reference statements)
7
55
0
Order By: Relevance
“…Additionally, no infants in our study had a fetal immune response to Spike protein as demonstrated by a negative anti-SARS-CoV-2 IgM antibody in cord blood and infant follow up samples. This further supports the lack of transfer of vaccine products, as only IgG is transferred from the mother, and IgM production would indicate an endogenous fetal immune response which has rarely been seen in natural infection with SARS-CoV-2 during pregnancy 16,[21][22][23] . This provides additional reassurance that mRNA vaccination is safe during pregnancy.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Additionally, no infants in our study had a fetal immune response to Spike protein as demonstrated by a negative anti-SARS-CoV-2 IgM antibody in cord blood and infant follow up samples. This further supports the lack of transfer of vaccine products, as only IgG is transferred from the mother, and IgM production would indicate an endogenous fetal immune response which has rarely been seen in natural infection with SARS-CoV-2 during pregnancy 16,[21][22][23] . This provides additional reassurance that mRNA vaccination is safe during pregnancy.…”
Section: Discussionmentioning
confidence: 53%
“…This is consistent with known persistence of maternally-derived antibodies from other vaccinations including pertussis, rubella, varicella [24][25][26] . Additionally, we have previously found persistence of anti-SARS-CoV-2 IgG antibodies in infants after natural infection up to 6 months 16 . However, the functional capability of these antibodies as compared to anti-SARS-CoV-2 vaccination-derived antibodies is unknown.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, the transmission rate of SARS-CoV-2 S antibody was associated with the severity of the disease as reported by previous studies [ 15 , 28 , 29 ]. A recent cohort study including 145 mothers with SARS-CoV-2 infection indicated that the transfer rate was higher in infected women in the second trimester or women with onset of infection more than 60 days before delivery [ 30 ]. The extent to which vertical transmission of maternal acquired antibodies in response to SARS-CoV-2 infection during pregnancy is a key factor for understanding possible neonatal protection to develop efficient vaccination strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer ratios increase with increasing time between onset of maternal infection and delivery with maximum at 60−180 days before delivery. 52 55 Thus, maternal vaccination may protect the infant after an adequate interval from vaccination to delivery (of at least 4 weeks). 56 Maternally derived anti-SARS-CoV-2 IgG may persist in infants up to 6 months of life.…”
Section: Potential Strategies In Prevention Of Perinatal and Neonatal Covid-19mentioning
confidence: 99%